A MODERN APPROACH TO THE STABILIZATION OF THE DENTAL ARCH IN PERIODONTITIS USING THERMOPLASTIC MATERIALS (Eureka Journal of Physical and Chemical Research, 2025)
The aim of the present study was to evaluate the effectiveness of a therapeutic and preventive splinting construction developed for the stabilization of teeth in patients with early and moderate stages of periodontitis. Mathematical modeling and biomechanical analysis were applied, enabling a quantitative assessment of functional load redistribution within the dentoalveolar system when using the proposed construction.A thermoplastic polymer, Vetakryl, characterized by high biocompatibility, elasticity, and resistance to deformational loads, was used as the splinting material. Comparative analysis of the mechanical properties of Vetakryl and conventional cobalt–chromium alloys demonstrated the advantages of the new material in reducing stress concentration and improving the uniform transmission of masticatory forces.The results of mathematical modeling were confirmed by clinical observations: the use of the Vetakryl-based construction contributed to a reduction in tooth mobility, a decrease in inflammatory manifestations, improvement of periodontal functional status, and increased stability of the dental arch.The developed methodology can be recommended for clinical application in the treatment and prevention of periodontal diseases, as well as serving as a model for further investigations into the biomechanical properties of dental constructions.
Keywords: Periodontitis, splinting construction, Vetakryl, thermoplastic polymer, mathematical modeling, biomechanical analysis, functional load.